2009
DOI: 10.2174/138161209788453248
|View full text |Cite
|
Sign up to set email alerts
|

Scientific and Clinical Challenges in Sepsis

Abstract: Advances in intensive care and antibiotics have prevented the spread of some infections, though sepsis mortality rates remain high. With failure of over thirty clinical trials, sepsis remains a scientific and clinical challenge in modern medicine. Sepsis is defined by the clinical signs of a systemic inflammatory response to infection. “Severe sepsis” is when these symptoms are associated with multiple organ dysfunction. These definitions of sepsis may be too broad and common to heterogeneous groups of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 203 publications
(312 reference statements)
0
45
0
Order By: Relevance
“…Yet, in addition to coagulation activation and the downregulation of endogenous anticoagulant pathways, impairment of the fibrinolytic system plays a central role in the pathogenesis of microvascular thrombosis and organ dysfunction in sepsis. 8,9,12,13 To date, the mechanisms that modulate fibrinolysis in sepsis remain incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, in addition to coagulation activation and the downregulation of endogenous anticoagulant pathways, impairment of the fibrinolytic system plays a central role in the pathogenesis of microvascular thrombosis and organ dysfunction in sepsis. 8,9,12,13 To date, the mechanisms that modulate fibrinolysis in sepsis remain incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,12,13 To date, the mechanisms that modulate fibrinolysis in sepsis remain incompletely understood.…”
Section: Dna Impairs Fibrinolysis In Sepsis 2549mentioning
confidence: 99%
See 1 more Smart Citation
“…These treatments, however, have yielded variable effects on the resolution of sepsis complications and survival. Drotrecogin alfa (recombinant human-activated protein C) is currently the only treatment for sepsis approved by the Food and Drug Administration ( 27 ). The PROWESS study showed that this treatment improved survival in high-risk patients ( 28 ).…”
Section: Vessel Reactivity Studiesmentioning
confidence: 99%
“…While recombinant activated protein C (APC, also known as Drotrecogin alpha-activated) is currently the only FDA-approved therapy for sepsis, it is only indicated in patients at the late stage of severe sepsis [134]. Ultimately, the most successful therapies will in all probability be those that can be implemented as early as possible.…”
Section: Sepsis Therapiesmentioning
confidence: 99%